2002
DOI: 10.1046/j.0306-5251.2001.01516.x
|View full text |Cite
|
Sign up to set email alerts
|

St John's Wort increases expression of P‐glycoprotein: Implications for drug interactions

Abstract: Aims St John's Wort (SJW) is widely used in the treatment of depression but concerns have been raised about its potential to interact with other drugs. Co-administration with SJW has resulted in signi®cant reductions in trough plasma concentrations of indinavir and cyclosporin [1,2]. Induction of cytochrome P450 3A4 (CYP3A4) has been implicated as the most likely interaction mechanism. However, the magnitude of the interaction seen in clinical practice is greater than that predicted by in vitro studies suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
134
0
7

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(146 citation statements)
references
References 52 publications
5
134
0
7
Order By: Relevance
“…[233] Induction of CYP3A and/or P-glycoprotein was suggested in the interaction of St John's wort and IDV, in which St John's wort reduced the AUC of IDV by 57% (table III). [208,234] That herbal agents are not as harmless as generally thought is also illustrated by clinically important interactions observed with garlic supplements and grapefruit juice (table III). In a study in healthy volunteers, garlic supplements administered twice daily for 20 days resulted in a 51% reduction in the AUC of SQV, probably by induction of CYP enzymes.…”
Section: Tdm Idv Recommendedmentioning
confidence: 99%
“…[233] Induction of CYP3A and/or P-glycoprotein was suggested in the interaction of St John's wort and IDV, in which St John's wort reduced the AUC of IDV by 57% (table III). [208,234] That herbal agents are not as harmless as generally thought is also illustrated by clinically important interactions observed with garlic supplements and grapefruit juice (table III). In a study in healthy volunteers, garlic supplements administered twice daily for 20 days resulted in a 51% reduction in the AUC of SQV, probably by induction of CYP enzymes.…”
Section: Tdm Idv Recommendedmentioning
confidence: 99%
“…Using purified polyphenols on Pgp overexpressing cells in vitro, Patel et al [59] showed that quercetin, hypericin and kaempferol were able to increase the cellular uptake of ritonavir by five-to eightfold. It is also interesting to note that in vitro assays or short-term exposure to these polyphenols in vivo appears to inhibit the action of efflux pumps and increase substrate bioavailability, whilst chronic exposure in healthy volunteers actually increases the expression of Pgp and, hence, reduces the bioavailability of efflux pump substrate drugs [14,27].…”
Section: Modulation Of Gut Mao Enzymesmentioning
confidence: 99%
“…P-glycoprotein (Pgp/ MDR1), MRP2 and BCRP are localised in the apical membrane, effluxing compounds back in to the gut lumen; whereas MRP1, 3 and 5 are localised in the basolateral membranes pumping substrates in to the blood stream. MRP4 is present in both the apical and basolateral membranes of gut epithelia [6] chronic exposure to some polyphenol efflux pump inhibitors may actually increase transporter expression over time [14,27].…”
Section: Polyphenols As Abc Transporter Substratesmentioning
confidence: 99%
“…Pesquisadores da Universidade de Zurique (Suíça) mostraram que a erva interfere no efeito imunossupressor da ciclosporina, utilizado na prevenção de rejeição a órgãos transplantados, (Baede Van Dijk et al, 2000;Breidenbach et al, 2000;Moore et al, 2000;Ruschitzka, et al 2000;Moschella e Jaber, 2001;Hennessy et al, 2002). A queda nos níveis séricos de ciclosporina e a rejeição de órgãos ou tecidos transplantados, podem ocorrer em poucas semanas após o uso concomitante de extrato de hipérico.…”
Section: Hypericum Perforatum Linaeusunclassified